Safety and Effectiveness of Silicone Gel–Filled Breast Implants in Primary Augmentation Patients. (27th February 2021) - Maxwell, Daniel; Estes, Megan; Walcott, Jennifer McMillen; Canady, John W; Hunter, Tina D; Gache, Larry; Wang-Ashraf, Bernadette; Alexander, Diane
Abstract: Background: Results from the MemoryGel Breast Implants Core Clinical Study suggest these devices are safe and effective at 10 years after implantation. Although clinical trials are essential for measuring the safety and effectiveness of a device, real-world evidence can supplement clinical trials by providing information on outcomes observed in diverse clinical settings for a more heterogeneous population, without fixed treatment patterns, and without continuous patient monitoring, such that follow-up is more representative of normal clinical practice. Objectives: The aim of this study was to measure real-world outcomes, including safety and effectiveness, in patients who underwent primary breast augmentation with smooth MemoryGel implants. Methods: This was a case series looking at patients, age 22 years and older, who underwent primary breast augmentation at a single site between December 2006 and December 2016 and who had a minimum of 2 years of follow-up. Descriptive statistics were used to summarize baseline characteristics and outcomes. Kaplan-Meier models were used to estimate safety outcomes for capsular contracture (Baker grade III/IV), infection, and rupture. Results: A total of 50/777 (6.4%) patients reported a complication, with an average time to complication of 3.9 years (range, 19 days-11.8 years) postprocedure. Kaplan-Meier estimates of the 10-year cumulative incidence of capsular contracture (Baker grade III/IV), infection, and rupture were 4.7%, 0.1%, and 1.6%, respectively. Conclusions: Analyses of a large population from a single site provide further support for the long-term safety and effectiveness of MemoryGel breast implants in a primary augmentation cohort. Level of Evidence: 4: